(untitled) (Mother Language, 2025)
English research extensively uses technology for error checking and citation, a support largely unavailable for Bangla research, hindering quality assessment against global benchmarks. This study explores Bangla-writing researchers’ attitudes toward the use of online technology in their scholarly works, measure the marginal effects of using online technology in Bangla scholarly works, and identify essential contributors to the use of online technology. A questionnaire survey, employing convenience sampling, was conducted among students and teachers (n = 177) in Pabna city. To empirically assess the factors influencing writing quality, a logit model was employed. The results indicate that online technologies, workshop on use of online technologies, and natural language processing tools are statistically significant and have the potential to improve Bangla scholarly writing. However, realizing this potential necessitates addressing current challenges in the proper and efficient usage of available software and exploring the development and adoption of more tailored technological solutions for the Bangla scholarly community. Mother Language, 2025; 9(1): 73-106